EKSISTENSI INVERS GRUP DARI MATRIKS BLOK - Riana Wendya; Rolan Pane; Musraini .M (Jurnal Online Mahasiswa (JOM) Bidang Matematika dan Ilmu Pengetahuan Alam, 2014)
We discuss necessary and sufficient conditions for the existence of the group inverse of block matrices of the forms M and , where A, B are square matrices with . In addition, we also give two explicit forms of the considered block matrices.